A surgical sealant, AQUABRID decreased the volume of intraoperative blood transfusions and operative time for acute aortic dissection repair. Issue 12 (15th November 2022) - Matsuoka, Tadashi; Hashizume, Kenichi; Koizumi, Kiyoshi; Funaishi, Koji; Kuroo, Kento; Kaneyama, Hiroaki; Takaki, Hidenobu; Mori, Mitsuharu; Lefor, Alan Kawarai; Shimizu, Hideyuki; Sasaki, Junichi
Abstract: Background: The effect of the surgical sealant AQUABRID on outcomes after acute aortic dissection repair has not been evaluated. The objective of this study was to examine whether the use of AQUABRID affects the volume of intraoperative blood transfusion or operative time in patients undergoing emergency surgery to repair acute aortic dissection. Methods: A multicenter retrospective cohort study from January 2007 to December 2021. A total of 399 patients underwent emergency acute aortic dissection repair. Propensity score matching was used to adjust for the type of surgery and other patient characteristics. Results: A total of 387 of the eligible 399 patients were included in this study and propensity score matching yielded 94 patients for whom characteristics were not significantly different between the two groups. The type of surgery was exactly matched (ascending aorta replacement: 19 [40%]; partial arch replacement: 13 [28%]; total arch replacement: 15 [32%] in each group). Within the matched cohort, there was a statistically significant difference in the volume of intraoperative blood transfusion. (AQUABRID vs. control: 34 [26–38] vs. 50 [38–60] U in Japan, p  = .03). Operating time was significantly shorter in the AQUABRID group (total operation: mean ± SD, 343 ± 92 vs. 402 ± 161 min, p  = .03; reconstruction for arch vessels: 29 ± 17 vs. 56 ± 22, p  < .01). The rate of postoperative complications was comparable in the two groups. Failure to use AQUABRID was a significant predictor of the need for massive transfusion (>40 U) (odds ratio: 7.20; 95% confidence interval: 2.56–20.23; p  < .01). Conclusions: The use of AQUABRID during emergency acute aortic dissection repair significantly decreased the volume of intraoperative blood transfusion and the duration of surgery.